ASSESSMENT OF THE GEOSPATIAL DISTRIBUTION OF LIVESTOCK RESOURCES AND INFRASTRUCTURES IN NIGERIA - Baba, D.; Tijani, A.A.; Sale, N.A.; Adebowale, W.A.; Durojaiye, L.; Aliyu, M.D.; Aliyu, A.M.; Bello, M.; Mohammed, T.; Matazu, M.B.; Othman, M.K. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
This paper employs data from the Livestock Productivity and Resilience Support (L-PRES) baseline survey (October, 2024– February, 2025), which combined household-level information with geospatial mapping, to examine the spatial allocation of resources and its impact on production outcomes. A total of 7,020 households from 156 Local Government Areas were surveyed, while infrastructure facilities were georeferenced and analyzed using ArcGIS and QGIS tools. The results show highly uneven distributions: grazing reserves (81.6%) and water points (73.1%) are concentrated in the north, while feed mills (68.4%) and veterinary clinics (49.8%) are predominantly in the south. Livestock markets, though denser in the north, are undermined by insecurity and poor infrastructure. Chi-square tests confirmed strong statistical associations between region and resource distribution (χ² = 740.39, p < 0.001), validating that disparities are systemic rather than random. Productivity assessments reveal that northern zones, despite having larger herds, face gaps of 18–32% compared to southern systems, largely due to limited veterinary services and weak feed supply. Conversely, southern poultry and small ruminant systems thrive under better service coverage and commercialization. While access to veterinary services showed only marginal statistical significance (χ² = 5.39, p = 0.067), trends consistently demonstrate its role in boosting productivity. The paper concludes that addressing regional imbalances through targeted investments, especially in northern states, is essential for improving national livestock productivity and resilience.